An Identity-Based Blind Signature Scheme Using Lattice with Provable Security. (11th May 2020) - Li, Quanrun; Hsu, Chingfang; He, Debiao; Choo, Kim-Kwang Raymond; Gong, Peng
Abstract : With the rapid development of quantum computing and quantum information technology, the universal quantum computer will emerge in the near decades with a very high probability and it could break most of the current public key cryptosystems totally. Due to the ability of withstanding the universal quantum computer's attack, the lattice-based cryptosystems have received lots of attention from both industry and academia. In this paper, we propose an identity-based blind signature scheme using lattice. We also prove that the proposed scheme is provably secure in the random oracle model. The performance analysis shows that the proposed scheme has less mean value of sampling times and smaller signature size than previous schemes. Thus, the proposed scheme is more suitable for practical applications.